A Binding Kinetics Study of Human Adenosine A(3) Receptor Agonists - Xia, Lizi (Biochem Pharmacol, 2018)
The human adenosine A(3) (hA(3)) receptor has been suggested as a viable drug target in inflammatory diseases and in cancer. So far, a number of selective hA(3) receptor agonists (e.g. IB-MECA and 2-Cl-IB-MECA) inducing anti-inflammatory or anticancer effects are under clinical investigation. Drug-target binding kinetics is increasingly recognized as another pharmacological parameter, next to affinity, for compound triage in the early phases of drug discovery. However, such a kinetics-driven analysis has not yet been performed for the hA(3) receptor. In this study, we first validated a competition association assay for adenosine A(3) receptor agonists to determine the target interaction kinetics. Affinities and Kinetic Rate Index (KRI) values of 11 ribofurano and 10 methanocarba nucleosides were determined in radioligand binding assays. Afterwards, 15 analogues were further selected (KRI <0.70 or KRI >1.35) for full kinetics characterization. The structure-kinetics relationships (SKR) were derived and longer residence times were associated with methanocarba and enlarged adenine N(6) and C2 substitutions. In addition, from a k(on)-k(off)-K(D) kinetic map we divided the agonists into three subgroups. A residence time “cliff” was observed, which might be relevant to (N)-methanocarba derivatives' rigid C2-arylalkynyl substitutions. Our findings provide substantial evidence that, next to affinity, additional knowledge of binding kinetics is useful for developing and selecting new hA(3)R agonists in the early phase of the drug discovery process.